Employee Development: New Paradigms. Issue 3 (July 2022) - Sachdev, Anil
Employees are the life of any organisation. The success or failure of the organisation depends on employee engagement, motivation and performance. Organisations are investing huge amounts of time, money and resources on employee development. This paper analyses and shares some frameworks and models related to employee development with various live examples of B-school programmes, executive learning strategies and organisational initiatives. It refers to the mega trends shaping the world due to the COVID-19 pandemic and develops a model for creating meaningful and competent teams for development needs and the potential identification and proper execution of employee development strategies. This article also talks about how technology can be used for development needs identification and capability building. The article suggests that we should look at various dimensions like conceptual skills, technical and functional skills, human skills, curiosity, self-awareness and corporate citizenship, while designing employee development programmes.